PENGARUH EFEKTIVITAS DAN EFISIENSI KERJA PEGAWAI TERHADAP KINERJA ORGANISASI DINAS SOSIAL KOTA KENDARI - Muhammad Basri; Rosfiah Arsal (Journal Publicuho, 2022)
This study aims to examine the effect of work effectiveness and efficiency on organizational performance in the Social Agency of Kendari City. This type of data are quantitative data sourced from 49 respondents using questionnaires as a data collection technique. The data surveyed consisted of 16 dimensions from variables of work effectiveness, work efficiency and organizational performance. The data was processed using the SPSS Version 25 statistical package program and analyzed with multiple regressions. The results showed that the effectiveness and work efficiency of employees had a significant effect on the organizational performance of the Social Agency. The better of work effectiveness and efficiency of employee, the more positive impact on improving the current work of the organization which is characterized by increasing the quality and productivity of services, more creative innovation and the use of information systems to speed up and simplify work